The Feminine Genius of Catholic Theology - Levering, Matthew, 1971- (London ; New York : T & T Clark, 2012)
"Levering's book revolves around a beautifully simple device: he presents to us some of the great women of Christian history as teachers of the common Catholic faith. But in adopting this simple device, Levering attempts also to recast how we view the theology of such figures as Hildegard and Julian. For Levering, each of the figures he includes -- from Egeria in the fourth century Mediterranean world, to Edith Stein facing death at the hands of the Nazis -- writes from the heart of the Church. And thus this book is also a vision of the faith held by that Church, an introduction to Catholic theology itself."--P. 4 of cover.
Introduction -- God the Trinity -- Jesus Christ -- Creation and providence -- Sin -- Sacraments -- The Church -- The virtues -- Mary and the saints -- Prayer -- Eternal life.
Includes index.
Keywords: Catholic Church -- Doctrines; Women -- Religious aspects -- Catholic Church; Women in the Catholic Church; Catholic women -- Religious life; Feminist theology